Design of a real time modified linear Delta Modulator using TMS 320C6416 DSP processor - Thong, Chung Mun; Suardi, Kaharuddin; Farid, Ghani (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.